THE EFFECT OF ABDOMINAL MASSAGE AND KUNYIT ASAM HERBS TO REDUCE PRIMARY MENSTRUAL PAIN (DYSMENORRHEA) - Sumardiko, Dwi Setiani; Maulida Rizki Roswandi, Alyaa'; Purwitasari, Neny; Hamsidi, Rini (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: Menstrual pain (dysmenorrhea) is a cramp in the lower abdomen that occurs during menstruation, while menstrual pain that is experienced without any abnormality in the reproductive organ is called primary dysmenorrhea. Primary dysmenorrhea case experienced by the patient is complaints of pain in the lower part, sometimes spreading to the waist and feeling like pressure or squeezing which occurs within 1-2 days of menstruation. Purpose: Determine the effect of abdominal massage therapy and tamarind turmeric herbs on reducing primary dysmenorrhea. Case analysis: A case study for treating menstrual pain using abdominal massage and herbal methods. Abdominal massage therapy is performed on the abdominal area and herbal therapy is given to the patient, namely herbal turmeric (Curcuma longa Linn.) and tamarind fruit which have analgesic, antipyretic, and anti-inflammatory effects. Result: Turmeric and tamarind contain active compounds curcumin and anthocyanin which work together to inhibit cyclooxygenase (COX) reactions so that they can inhibit or reduce inflammation and uterine contractions which cause menstrual pain. The treatment for primary dysmenorrhea is abdominal massage therapy 14 times, once every 2 days for 30 days. Meanwhile, tamarind turmeric herbal therapy is given 2 times a day for 7 days before menstruation and the first 3 days during menstruation with a combination dose of 10 grams of turmeric rhizome and 5 grams of tamarind fruit. Conclusion: Abdominal massage therapy and tamarind turmeric herbs affect reducing menstrual pain in the case of primary dysmenorrhea.